Untitled (African Knowledges and the History Publication since the 1970s)
Miattah Fahnbulleh sings at Leisure Awards Dance nite Star Hotel; lunching of her Album 'Just for you'; a music video from her titled 'Jebe' and a basketball match between Detroit and Atlanta.
Keywords: Music; Sports